1997
DOI: 10.1200/jco.1997.15.6.2312
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, toxicity, and applicability of high-dose sequential chemotherapy as adjuvant treatment in operable breast cancer with 10 or more involved axillary nodes: five-year results.

Abstract: HDS therapy emerges as an effective and applicable regimen, whose major toxicity was occasional. Final assessment of its value in a randomized, multicenter trial is presently underway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
1
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(100 citation statements)
references
References 26 publications
8
88
1
3
Order By: Relevance
“…HD thiotepa has been associated with a 5% cardiac toxicity in two studies, 54,55 while other series did not confirm these findings. 8,25 HD ifosfamide cardiotoxicity is reported in only two studies more than 20 years old. 56,57 Anecdotal evidence is reported for HD carmustine-associated cardiac toxicity.…”
Section: Other Chemotherapeutic Agentsmentioning
confidence: 99%
See 3 more Smart Citations
“…HD thiotepa has been associated with a 5% cardiac toxicity in two studies, 54,55 while other series did not confirm these findings. 8,25 HD ifosfamide cardiotoxicity is reported in only two studies more than 20 years old. 56,57 Anecdotal evidence is reported for HD carmustine-associated cardiac toxicity.…”
Section: Other Chemotherapeutic Agentsmentioning
confidence: 99%
“…10 However, in recent years, the percentage of patients receiving singleagent HD cyclophosphamide up to 7 g/m 2 or 200 mg/kg experiencing cardiotoxicity has diminished to nearly zero with the adoption of multifractionated schedule of administration. 4,5,[7][8][9]25 Available evidence indicates that singleagent HD cyclophosphamide-associated cardiac toxicity is dose and schedule dependent, and it is not related to the cumulative drug dose. 13,16,21 No pharmacokinetic parameter has been consistently associated with cardiotoxicity, although a significant inverse association between a reduced HD cyclophosphamide area under the curve (AUC) (ie accelerated clearance due to an increased conversion to active metabolites) and cardiotoxicity was found in three independent studies, 17,26,27 but not confirmed in a larger one.…”
Section: Cardiac Toxicity Due To Conditioning Regimenmentioning
confidence: 99%
See 2 more Smart Citations
“…The OS is 68% [59]. Updated data from the second study discuss 67 patients treated with high-dose sequential cyclophosphamide, methotrexate, and melphalan with a median follow-up of 48.5 months and a lead follow-up of 78 months [60]. Actuarial relapse-free survival (RFS) is 57% and OS 70%.…”
Section: Hdc For High-risk Primary Breast Cancermentioning
confidence: 99%